The Relationship between Health Care Students' Attitudes Towards Gender Roles and Psychological Well-Being - Pelin PALAS (Muhammed Yıldız, 2020)
The research was carried out to determine the relationship between healthcare students' attitudes towards gender roles and their psychological well-being. The research is descriptive and progressive. The research was carried out in the Health Services Vocational School of a university in the fall semester of the 2019-2020 academic year. The sample of the study consisted of a total of 165 students studying in the First and Emergency Aid and Medical Documentation and Secretarial program. The data were collected with the Personal Introductory Information Form, the Attitude Scale for Gender Roles and the Psychological Well-Being Scale. The data of the study were evaluated in Independent Groups by t-test, One Way Variance Analysis and Pearson Correlation Tests. Health Services Vocational School students; it was determined that most of them were educated in the First and Emergency Programs, they were second class, they did not work and they lived in the nuclear family. The mean score of the Gender Attitude Scale of the students is 54.31 and the average score of the Psychological Well-Being Scale is 39.57. In this study, it was found that the attitudes of women and in the First and Emergency program students towards gender roles were significantly high. In the study, a positive weak correlation was found as a result of the correlation analysis conducted to evaluate the relationship between the students' gender roles attitude and psychological well-being (r=0.158; p=0.043<0.05). As a result, it is recommended to implement programs where students studying in health services can develop an egalitarian attitude, egalitarian perspective, awareness and sensitivity.